Development of an RME-Based Teaching E-Module in the Peatlands Context for Grade VIII SMP Pythagorean Theorem Material - Loy Cindy Br Milala; Setri Oktavia; Putri Sasalia S.; Emy Artuti (Journal of Instructional Mathematics, 2025)
This study aims to develop a mathematics teaching e-module based on the Realistic Mathematics Education (RME) approach within the peatlands context for Grade VIII students on the Pythagorean Theorem. The research applies nine stages of the Dick and Carey instructional design model: identifying instructional goals, conducting instructional analysis, analyzing learners and contexts, writing performance objectives, developing assessment instruments, designing instructional strategies, developing instructional materials, conducting formative evaluation, and revising instruction. The study involved 31 students and one mathematics teacher. Data were collected through expert validation sheets and response questionnaires for teachers and students. Expert validation results showed that all aspects of the e-module and student worksheet (LKPD) including content, context, evaluation, media, language, format, and layout achieved high validity. Teachers and students rated the product in the Good to Very Good category, which means the e-module and LKPD are feasible for classroom use. Revisions based on expert and user feedback made the Final Prototype clearer and more engaging. Overall, the study indicates that the RME-based e-module with a peatland context is valid, practical, and effective in improving students’ understanding of the Pythagorean Theorem throught contextual learning.